Pengaruh Rekrutmen, Pelatihan dan Kompensasi terhadap Kinerja Karyawan - Ndaru Agung Pamungkas; Nurti Widayati (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this study was to examine the effect of independent variable (X), which are Recruitment, Training, and Compensation on the dependent variabel (Y) Employee Performance of PT. Indi Platform Raksasa (S-gala.com) Bandung. The method used in this study is causality. This study uses purposive sampling. Respondents inolved in this study were 54 employees. Data collecting is by distributing quesionnaires. And the method for data analysis in this research is multiple linear regression processed with SPSS program version 25. Based on the hypothesis test the results of this study is Recruitment, Training, and Compesation affect the Employee Performance.